A comparative study of international recruitment – tensions and opportunities in institutional recruitment practice. Issue 2 (3rd July 2018) - James-MacEachern, Melissa
ABSTRACT: The purpose of this research is to explore international student recruitment at higher education institutions (HEIs) by examining the development and implementation of international recruitment activities. There is little research regarding the internal operations of HEIs, how HEIs conduct international recruitment efforts, and the challenges that international recruiters encounter. This study finds that although national policy frameworks vary by country, the practice of international recruitment remains remarkably similar amongst the case study institutions. It further suggests that regardless of rankings, HEIs are facing commodification within the international student recruitment market. Furthermore, it suggests that institutions may improve their recruitment activity by addressing role clarity, improving coordination, differentiating their offerings, and ensuring flexibility to respond to market forces.